Assessing the chronic barriers to justice faced by domestic violence survivors in the Western Cape - Grotzinger, Lior (Department of Public Law, 2025)
This dissertation examines the chronic barriers to justice faced by victims of domestic violence survivors in the Western Cape. It delves into the factors causing domestic violence survivors to disengage from the criminal justice system and investigates why many victims do not follow through with finalizing their protection orders. The high attrition rate in domestic violence cases in South Africa is a significant issue because it hinders the delivery of justice for victims and perpetuates cycles of abuse. When victims disengage from the criminal justice system or do not follow through with finalizing protection orders, they may remain in dangerous situations without adequate protection. This lack of closure and resolution can lead to continued incidents of abuse, putting victims' safety and well-being at risk. Additionally, the high attrition rate can erode trust in the justice system among domestic violence survivors, further discouraging them from seeking help in the future. Addressing this issue is crucial for providing effective support and protection to domestic violence survivors and holding perpetrators accountable for their actions. The study involved a thematic analysis of qualitative case notes recorded in 154 preselected case files, with data entry completed using Survey Monkey. The case files were collected by MOSAIC staff between January 2022 and December 2022. The survey encompassed 16 questions, targeting various aspects such as court location, follow-up reachability by MOSAIC, client engagement with SAPS for case filing, court appearance on designated dates, type of abuse experienced by clients, and reasons behind incomplete protection order processes. The data indicates that survivors refrained from reporting domestic violence to SAPS due to unfair and arbitrary treatment by SAPS officials. Furthermore, survivors often decide not to finalize protection orders when abuse cases and the respondent's behavior improves. MOSAIC workers report that SAPS officials advised survivors to obtain a restraining order first because they take back their abusers which results in wasted time and resources. Additionally, the data also highlights that some clients are unaware of the processes that need to be followed when dealing with protection order violations. Clients are also unaware of their option to reapply for an interim protection order if they have withdrawn their application or missed the return date, leading to a miscarriage of justice. The MOSAIC Court Case Monitoring Officer contacts clients seeking assistance to ensure they have received the necessary services. However, clients are at varying stages in the protection 9 order process, and many do not return after receiving an interim or final protection order. This causes challenges in tracking clients through the justice system and assessing whether they have received the required support. A reduction in the high attrition rate in domestic violence cases can be achieved through SAPS officials demonstrating more compassion and understanding, as mandated by the Domestic Violence Act 116 of 1998 (DVA) and the Domestic Violence Amendment Act 14 of 2021 (DVAA). Additionally, an improved understanding of the interim and final protection order process by applicants is crucial. Keywords: domestic violence, interim protection order, final protection order, chronic barriers